Earth Polychromatic Imaging Camera Geolocation; Strategies to Reduce Uncertainty - Blank, Karin; Huang, Liang-Kang; Herman, Jay; Marshak, Alexander (Frontiers in Remote Sensing, 2021)
EPIC (Earth Polychromatic Imaging Camera) occupies a unique point of view for an Earth imager by being located approximately 1.5 million km from the planet at Earth-Sun Lagrange point, L1. This creates a number of unique challenges in geolocation, some of which are distance and mission specific. To solve these problems, algorithmic adaptations need to be made for calculations used for standard geolocation solutions, as well as artificial intelligence-based corrections for star tracker attitude and optical issues. This paper discusses methods for resolving these issues and bringing the geolocation solution to within requirements.